It's More the Exception Rather Than the Rule: African American Families' Neighborhoods and Youth's Academic Performance During Middle School. (September 2018) - Witherspoon, Dawn P.; Rivas-Drake, Deborah; Banerjee, Meeta
Neighborhoods are an important part of the social milieu of adolescence and academic performance. Using experiential neighborhood profiles, this study examined risks and assets to determine how neighborhood structural and relational dynamics were associated with academic achievement during early adolescence. The sample included 723 African American socioeconomically diverse families ( M youth age = 12.27 years, SD = 0.55). Results showed that neighborhood structural disadvantage was unrelated to academic achievement, whereas neighborhood profiles were associated with academic performance in eighth grade, after adjusting for seventh grade GPA. Neighborhood profiles characterized by positive social relationships were associated with higher achievement. Authors discuss the importance of examining neighborhood risks and supports for African American youth's academic adjustment.